Outbreak Investigation of NADC30‐Like PRRSV in South‐East China. Issue 5 (13th June 2016) - Li, C.; Zhuang, J.; Wang, J.; Han, L.; Sun, Z.; Xiao, Y.; Ji, G.; Li, Y.; Tan, F.; Li, X.; Tian, K.
Summary: Epidemiological outbreak investigations were conducted on NADC30‐like porcine reproductive and respiratory syndrome virus (PRRSV) to investigate the prevalence of the disease in south‐east China in 2015. Two more provinces were found to have NADC30‐like PRRSV circulating besides previously reported six provinces. Phylogenetic analysis showed that these virus isolates were clustered in an independent branch and shared high nucleotide similarity to NADC30, a type 2 PRRSV that has been isolated in Unite States in 2008. One NADC30‐like PRRSV strain from Henan province was successfully isolated on porcine alveolar macrophages and was tested on 6‐week‐old specific pathogen‐free pigs for pathogenic study. The virus‐inoculated pigs showed typical PRRSV clinical symptoms, but all pigs survived throughout the study with a period of 14 days. At necropsy, the lungs of infected pigs developed PRRSV‐specific interstitial pneumonia, and virus antigen was detected in lung samples. Therefore, our results indicated NADC30‐like PRRSV has widely spread in China and could cause clinical disease on pigs.